An Incidental Large Rectal Polyp with Idiopathic Small Arteriovenous Dysplasia in Colonic Submucosa: A Case Report - Yang, MD, Patrick; Sarka, MD, Avik; Han, MD, PhD, Liying; Zhou, MD, PhD*, Zhongren (North American Journal of Medicine and Science, 2024)
Rectal polyps with idiopathic small arteriovenous dysplasia are rare. The mesenteric vascular diseases were recently classified as two vascular diseases: fibromuscular dysplasia (FMD) of artery and mesenteric arteriovenous dysplasia/vasculopathy (MAVD/V). FMD usually involves medium size mesenteric arteries in younger individuals. In contrast, MAVD/V tends to affect multiple small mesenteric arteries and veins without vascular lesions in other organs. We reported that a 45-year-old male with a large rectal polyp for routine colorectal screening. Microscopic examination shows chronic ischemic changes and multiple small arteries, veins and capillaries with intimal and medial hyperplasia and focal occlusion, mimicking mesenteric arteriovenous dysplasia and named it as submucosal arteriovenous dysplasia. [N A J Med Sci. 2024;17(1):001-003. DOI: 10.7156/najms.2024.1701001]